Assessment of physical activity among pregnant women in Hospital USM - Zaman, Nik Farhana Nik Khairu (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Controlling weight gain during pregnancy is important and of public health concern because excess weight gain during pregnancy could be the signal of the onset of ‘creeping obesity’. Women who were active doing exercise had a low risk of excessive gestational weight gain than women who were had sedentary lifestyle. Hence, this cross sectional study was carried out to examine physical activity and also to investigate the association between physical activity and gestational weight gain among pregnant women. A total of 149 pregnant women that aged 19 to 40 years from the Obstetrics & Gynaecology Clinics at Hospital USM, Kubang Kerian, Kelantan were selected. Participants self-administered the Pregnancy Physical Activity Questionnaire (PPAQ) and height and pre-pregnancy weight were taken from either medical record or selfreported to calculate pre-pregnancy body mass index (BM1). The gestational weight gain was determined using the 2009 Institute of Medicine (IOM) guidelines. The results showed that among 149 respondents, 27.5% was in second trimester while another 72.5% was in third trimester of pregnancy and most of the respondents did not achieve the recommended weight gain rate. Half of respondents engaged with exercise before getting pregnant but during pregnancy less than 20% of them were exercising. Fear of injuries or danger plus lack of time were the main reasons given by respondents for not exercising. The results from PPAQ showed that household activity calculated in MET hour/week constituted the largest amount of energy expenditure among respondents. Meanwhile, an evaluation of respondent’s activity according to classes of intensity showed that light activity constituted the highest amount of energy expenditure among respondents. respondents. There was no significant correlation between total energy expenditure and weight gain among these pregnant women (r = -0.009, p = 0.92). However, there was a decrease in physical activity intensities from second trimester to third trimester of pregnancy. But, the difference was statistically significant only for sedentary activity (p - 0.037). In conclusion, although the result showed that there is no association between energy expenditure and gestational weight gain, other studies had suggested that physical activity can reduce risk of excessive gestational weight gain. Therefore, further studies need to be carried out in local setting in order to confirm the current findings.